A Phase 2, Randomized, Active-controlled, Observer-blinded Study to Assess the Immunogenicity, Tolerability and Safety of Bivalent rLP2086, a Meningococcal Serogroup B Vaccine, Coadministered With Tetanus, Diphtheria and Acellular Pertussis Vaccine and Serogroup A, C, Y and W-135 Meningococcal Conjugate Vaccine in Healthy US Adolescents. Issue 6 (June 2016) - Muse, Derek; Christensen, Shane; Bhuyan, Prakash; Absalon, Judith; Eiden, Joseph J.; Jones, Thomas R.; York, Laura J.; Jansen, Kathrin U.; O'Neill, Robert E.; Harris, Shannon L.; Perez, John L.
Abstract : Background: Bivalent rLP2086, targeting meningococcal serogroup B, will extend prevention of meningococcal disease beyond that provided by quadrivalent serogroup ACWY vaccines; coadministration with recommended vaccines may improve adherence to vaccine schedules. This phase 2, randomized, active-controlled, observer-blinded study assessed whether immune responses induced by coadministration of Menactra (meningococcal A, C, Y and W-135 polysaccharide conjugate vaccine [MCV4]) and Adacel (tetanus toxoid, reduced diphtheria toxoid, acellular pertussis vaccine [Tdap]) with bivalent rLP2086 (Trumenba [meningococcal serogroup B vaccine], approved in the United States) were noninferior to MCV4 + Tdap or bivalent rLP2086 alone. Methods: Healthy adolescents aged 10 to <13 years received MCV4 + Tdap + bivalent rLP2086, MCV4 + Tdap or bivalent rLP2086. Bivalent rLP2086 response was assessed with serum bactericidal assays using human complement with 2 meningococcal serogroup B test strains expressing vaccine-heterologous factor H–binding protein variants; MCV4 with SBAs using rabbit complement; and Tdap with multiplexed Luminex assays. Safety was evaluated. Results: Two thousand six hundred forty-eight subjects were randomized. Immune responses to MCV4 + Tdap + bivalent rLP2086 were noninferior to MCV4 + Tdap or bivalent rLP2086 alone. Seroprotective serum bactericidal assays using human complement titers were documented for 62.3%–68.0% and 87.5%–90% of MCV4 + Tdap + bivalent rLP2086 recipients after doses 2 and 3, respectively. A ≥4-fold rise in serum bactericidal assays using human complement titers from baseline was achieved by 56.3%–64.3% and 84.0%–85.7% of subjects after doses 2 and 3, respectively. Bivalent rLP2086 alone induced similar responses. Concomitant administration did not substantially increase reactogenicity compared with bivalent rLP2086 alone. Conclusions: Bivalent rLP2086 given concomitantly with MCV4 + Tdap met all noninferiority immunogenicity criteria without a clinically meaningful increase in reactogenicity. MCV4 and bivalent rLP2086 coadministration would provide coverage against the 5 major disease-causing serogroups. Abstract : Supplemental Digital Content is available in the text.